Influencer marketing in the purchase decision of generation Z - Estrada, Isaac Cruz; Zavala, Ana María Miranda (International Journal of Innovative Research and Scientific Studies, 2025)
The objective of the research is to analyze the factors of influencer marketing associated with the purchase decision of Generation Z consumers. The study design begins with the literature review that supports the components of influencer marketing that motivate the purchase decision of Generation Z individuals. The methodology used for obtaining data from the target population is quantitative; a sample of 600 questionnaires was obtained and applied to people from Generation Z aged between 18 and 29 years. A descriptive analysis was carried out, and factor analysis was applied. Results: three factors were found which are fundamental in the purchase decision: 1) empathy of the influencer; 2) perception of reciprocity and benefits of the influencer; 3) consistency of the influencer. As the influencer develops these elements with greater credibility, authenticity, and creativity, they will be able to more effectively persuade the purchase decision of this sector of the population, adding brand value by connecting through their content with Generation Z. This intangible asset is useful for maintaining audience loyalty for a longer period.